Effect of Two Stages Artificial Ageing on Microstructure and Mechanical Behavior of Lm 25 Aluminium Alloy. Issue 1 (December 2020) - Bhaskara Raju, VVS; Sevanam, Sambi Reddy; Varadala, Ananda Babu; Chitturi, Suresh
Abstract: In the present investigation the influence of two stages artificial ageing, 1 st stage at 160°C followed by 2 nd stage at 140°C on microstructure and mechanical properties of LM 25 alloy was studied. It is observed that the microstructure changed under the influence of two stages ageing. It is also observed that the decrease in ageing temperature in the second stage, increases mechanical properties of the alloy. The tensile strength of the alloy in single stage ageing at 160°C is studied and compared with two stages ageing.